Enantioselective Organocatalyzed Formal [4+2] Cycloaddition of Ketimines with Allenoates: Easy Access to a Tetrahydropyridine Framework with a Chiral Tetrasubstituted Stereogenic Carbon Center. Issue 4 (16th January 2014) - Takizawa, Shinobu; Arteaga, Fernando Arteaga; Yoshida, Yasushi; Suzuki, Michitaka; Sasai, Hiroaki
Abstract Enantioselective organocatalytic synthesis of tetrahydropyridines bearing a chiral tetrasubstituted carbon stereogenic center has been achieved. The spiro‐type monoaryl phosphine catalyst, (R)‐SITCP, was found to promote the formal [4+2] cycloaddition of saccharin‐derived ketimines and α‐methyl allenoate to afford the corresponding six‐membered N‐heterocycles in high yields and excellent regioselectivities with up to 93% ee.